The protist Trichomonas vaginalis harbors multiple lineages of transcriptionally active Mutator-like elements - Lopes, Fabricio R. [UNESP]; Silva, Joana C.; Benchimol, Marlene; Costa, Gustavo G. L.; Pereira, Goncalo A. G.; Carareto, Claudia M. A. [UNESP] (Biomed Central Ltd., 2009)
Background: For three decades the Mutator system was thought to be exclusive of plants, until the first homolog representatives were characterized in fungi and in early-diverging amoebas earlier in this decade.Results: Here, we describe and characterize four families of Mutator-like elements in a new eukaryotic group, the Parabasalids. These Trichomonas vaginalis Mutator-like elements, or TvMULEs, are active in T. vaginalis and patchily distributed among 12 trichomonad species and isolates. Despite their relatively distinctive amino acid composition, the inclusion of the repeats TvMULE1, TvMULE2, TvMULE3 and TvMULE4 into the Mutator superfamily is justified by sequence, structural and phylogenetic analyses. In addition, we identified three new TvMULE-related sequences in the genome sequence of Candida albicans. While TvMULE1 is a member of the MuDR clade, predominantly from plants, the other three TvMULEs, together with the C. albicans elements, represent a new and quite distinct Mutator lineage, which we named TvCaMULEs. The finding of TvMULE1 sequence inserted into other putative repeat suggests the occurrence a novel TE family not yet described.Conclusion: These findings expand the taxonomic distribution and the range of functional motif of MULEs among eukaryotes. The characterization of the dynamics of TvMULEs and other transposons in this organism is of particular interest because it is atypical for an asexual species to have such an extreme level of TE activity; this genetic landscape makes an interesting case study for causes and consequences of such activity. Finally, the extreme repetitiveness of the T. vaginalis genome and the remarkable degree of sequence identity within its repeat families highlights this species as an ideal system to characterize new transposable elements.